Gender difference in health seeking behaviour among mothers of under five children in Lucknow - Katiyar, Rahul; Ahmed, Naim; Singh, Jai Veer; Singh, Vijay Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Discrimination and gender gaps have been observed even in early years of life. Although overall sex ratio in India has improved from 933 to 940 in the last decade, it declined from 927 to 914 in children aged less than five. Girls, less than five years, show steadily high mortality/morbidity compared to boys. This study was conducted to find the gender inequality in health seeking behaviour (HSB) among mothers of under five children. Methods: This community based cross sectional study was conducted in rural area of Lucknow, between September 2014 to August 2015. A total of 221 households having 376 under-five children were selected by multistage sampling technique from rural area of Lucknow. Mothers were interviewed about health seeking behavior for their ill child. Data were entered and analyzed using SPSS v21. Results: About 95% of the male child and 86.4% of the female child sought treatment. Of the total females that were treated, 67.3% were taken to a health facility/provider while the rest got treated at-home against 76.4% males that got treatment outside home. Conclusions: Gender discrimination do exist in the rural area at each step of seeking health-care for girl child. Adequate measures should be taken to improve their health status and consequently sex ratio as early as possible.